VARIABLES RELATED TO GINGIVITIS IN CHILDREN WITH PYELONEPHRITIS AND NEPHROTIC SYNDROME - Sirma T. Angelova (Peytchinski Publishing, 2021)
Purpose: The purpose of the research is to be investigated and assessed the significance of variables related to gingivitis in children with diagnosed pyelonephritis and nephrotic syndrome. Materials and Methods: The subject of the study is represented by participants in the age interval from 0 to 18 years. They are divided into two main groups, namely a group of 92 children with diagnosed pyelonephritis and 24 children with nephrotic syndrome. There is a group of 41 healthy children. Clinical, para-clinical, sociological and statistical methods are implemented in association with the study's aim. The model of the research is based on an investigation of the significance of definite variables: gingival index GI Lõe-Silness, level of salivary leucocytes, salivary blood and salivary glucose. In addition to these indicators are recorded some patterns of environmental matter. Results: Among the participants with the diagnosis of nephrotic syndrome is recorded the maximal value of GI= 2.04. A similar maximal value of GI=2.00 corresponds to the group of children with pyelonephritis. In both of the subgroups of children suffering from renal disorders is registered the considerable maximal value of salivary blood equal to 250.00 RBC/µl, compared to the maximal value of 50.00 RBC /µl for healthy participants. It is ascertained that the variables of salivary blood and salivary leucocytes correspond to the condition of gingivitis in children with diagnosed pyelonephritis and nephrotic syndrome. Conclusion: A definite impingement of excretory system disorders upon gingiva, especially among children suffering from nephrotic syndrome, is ascertained.